2020
DOI: 10.1371/journal.ppat.1008342
|View full text |Cite
|
Sign up to set email alerts
|

Structure and functional analysis of the Legionella pneumophila chitinase ChiA reveals a novel mechanism of metal-dependent mucin degradation

Abstract: Chitinases are important enzymes that contribute to the generation of carbon and nitrogen from chitin, a long chain polymer of N-acetylglucosamine that is abundant in insects, fungi, invertebrates and fish. Although mammals do not produce chitin, chitinases have been identified in bacteria that are key virulence factors in severe respiratory, gastrointestinal and urinary diseases. However, it is unclear how these enzymes are able to carry out this dual function. Legionella pneumophila is the causative agent of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 94 publications
0
54
0
1
Order By: Relevance
“…As such, it has been speculated that chitin may be used as an energy source by tick-borne bacterial pathogens [ 32 , 33 , 34 ]. Chitin cleavage can be performed by chitinases, and bacterial chitinases have been shown to promote bacterial persistence in marine environments and mammals [ 35 , 36 , 37 , 38 ]. Using a conserved domain search, we searched the Ft LVS genome for putative chitinases and, confirming a previous report [ 25 ], found that gene locus FTL1793 (annotated as a hypothetical protein) contains a region encoding a putative glycosyl hydrolase (GH) 18 chitinase D-like region ( Supplementary Figure S5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it has been speculated that chitin may be used as an energy source by tick-borne bacterial pathogens [ 32 , 33 , 34 ]. Chitin cleavage can be performed by chitinases, and bacterial chitinases have been shown to promote bacterial persistence in marine environments and mammals [ 35 , 36 , 37 , 38 ]. Using a conserved domain search, we searched the Ft LVS genome for putative chitinases and, confirming a previous report [ 25 ], found that gene locus FTL1793 (annotated as a hypothetical protein) contains a region encoding a putative glycosyl hydrolase (GH) 18 chitinase D-like region ( Supplementary Figure S5A ).…”
Section: Resultsmentioning
confidence: 99%
“…In Pseudomonas aeruginosa , a pulmonary pathogen, endochitinase activity correlates with antifungal activity, which may be important for microbial competition in the lung [ 76 ]. In Legionalla pneumophila , another pulmonary pathogen, the ChiA chitinase is required to cleave lung mucin and promote bacterial penetration through the alveolar mucosa [ 38 ]. Other bacterial chitinases have been shown to play similar roles in bacterial virulence, including cleavage of mammalian glycolipids, glycoproteins, and extracellular matrix components [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps host cargo adapters play a role in targeting LegC7 to ER exit sites and ER-derived compartments containing cargo beneficial to L. pneumophila during infection. Indeed, Emp46p and Emp47p are known to function in glycoprotein secretion [21], with a function similar to mammalian ERGIC-53/LMAN1 [41], and glycoprotein acquisition has been shown to be important for nutrition and evasion of host immune defenses by bacterial pathogens, including L. pneumophila [42][43][44]. While there is no documented role for ERGIC-53 in intracellular bacterial infection, this possibility should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although C1-INH is an inhibitor of complement activation, targeting C1-INH activity is used as a strategy for complement evasion by a range of different pathogens. Streptococcus pyogenes, and Legionella pneumophila use enzymes, SpeB and ChiA respectively, to cleave C1-INH (25,26), while Plasmodium falciparum, Borrelia recurrentis and Salmonella typhimurium depend on PfMSP3.1, CihC, and lipopolysaccharide (27)(28)(29), respectively to capture C1-INH on the cell surface. A hybrid of the above two strategies of C1-INH targeting has been proposed to be used by E. coli O157:H7 involving capture of C1-INH on the cell surface followed by an enzymatic cleavage (30).…”
Section: Inh Is Established As a Key Regulator Of Complement Via Inhimentioning
confidence: 99%